DC confidential : the controversial memoirs of Britain's ambassador to the U.S. at the time of 9/11 and the Iraq war - Meyer, Christopher, Sir (London : Weidenfeld & Nicolson, 2005)
As both the British ambassador to the US and as John Major's press secretary, Christopher Meyer has had unique access to the inner workings of government. In this book, he recalls close encounters with New Labour, the KGB and Bill Clinton, as well as the post 9/11 period and the relationship between Tony Blair and George W. Bush.
Includes index.
Keywords: Meyer, Christopher, Sir; Ambassadors -- Great Britain -- Biography